Recognition of Membrane Sterols by Polyene Antifungals Amphotericin B and Natamycin, A 13C MAS NMR Study - Ciesielski, Filip; Griffin, David C.; Loraine, Jessica; Rittig, Michael; Delves-Broughton, Joss; Bonev, Boyan B. (Frontiers in Cell and Developmental Biology, 2016)
The molecular action of polyene macrolides with antifungal activity, amphotericin B and natamycin, involves recognition of sterols in membranes. Physicochemical and functional studies have contributed details to understanding the interactions between amphotericin B and ergosterol and, to a lesser extent, with cholesterol. Fewer molecular details are available on interactions between natamycin with sterols. We use solid state 13C MAS NMR to characterise the impact of amphotericin B and natamycin on mixed lipid membranes of DOPC/cholesterol or DOPC/ergosterol. In cholesterol-containing membranes, amphotericin B addition resulted in marked increase in both DOPC and cholesterol 13C MAS NMR linewidth, reflecting membrane insertion and cooperative perturbation of the bilayer. By contrast, natamycin affects little either DOPC or cholesterol linewidth but attenuates cholesterol resonance intensity preferentially for sterol core with lesser impact on the chain. Ergosterol resonances, attenuated by amphotericin B, reveal specific interactions in the sterol core and chain base. Natamycin addition selectively augmented ergosterol resonances from sterol core ring one and, at the same time, from the end of the chain. This puts forward an interaction model similar to the head-to-tail model for amphotericin B/ergosterol pairing but with docking on opposite sterol faces. Low toxicity of natamycin is attributed to selective, non-cooperative sterol engagement compared to cooperative membrane perturbation by amphotericin B.